2017
DOI: 10.3892/etm.2017.5568
|View full text |Cite
|
Sign up to set email alerts
|

Anti‑tumour effects of polysaccharide extracted from Acanthopanax�senticosus and cell‑mediated immunity

Abstract: Abstract. Acanthopanax senticosus, also known as Siberian ginseng, is widely distributed throughout northern Asia and used in traditional Chinese medicine; it has been reported to prevent a number of diseases. However, the association between the antitumour and immunostimulatory activities of polysaccharide extracted from A. senticosus (ASPS) remains to be elucidated. The aim of the present study was to investigate the anti-tumour and immunomodulatory effects of polysaccharide extracted from ASPS on Crocker sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…For example, pharmacology study has shown that ADI contained a variety of polysaccharides including astragalus and acanthopanax senticosus which is refined and extracted by modern scientific methods. This can improve the phagocytosis of reticuloendothelial system, stimulate the production of TNF- α (tumor necrosis factor), and enhance the activity of T cells, NK cells, and Lak (lymphoid activated killer cells) of PHCC patients [ 35 37 ]. Furthermore, some researchers found that Ginseng (Rensheng) contains Rg3 and RH2 in Ginsenoside which can also enhance and improve the function of T cell and B cell, increase a number of interferon and interleukin, and enhance the killing ability of NK (natural killer) cells and lymphatic factor [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, pharmacology study has shown that ADI contained a variety of polysaccharides including astragalus and acanthopanax senticosus which is refined and extracted by modern scientific methods. This can improve the phagocytosis of reticuloendothelial system, stimulate the production of TNF- α (tumor necrosis factor), and enhance the activity of T cells, NK cells, and Lak (lymphoid activated killer cells) of PHCC patients [ 35 37 ]. Furthermore, some researchers found that Ginseng (Rensheng) contains Rg3 and RH2 in Ginsenoside which can also enhance and improve the function of T cell and B cell, increase a number of interferon and interleukin, and enhance the killing ability of NK (natural killer) cells and lymphatic factor [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“… 2017 ; Meng et al. 2017 ). Specifically, the following are the pharmacological effects of the active ingredients: (1) the sensitivity of hypoxic lung cancer cells can be increased, cisplatin resistance can be attenuated, and the immune response can be resumed by ginsenoside Rg3; (2) lung cancer cells usually migrate and invade in the body, which can be impaired by cantharidin ; (3) according to the activation of macrophages and natural killer cells, the polysaccharides extracted from Acanthopanax senticosus can inhibit tumour metastasis and play an antitumor role; (4) astragaloside IV can increase the sensitivity of NSCLC cells to gefitinib; (5) under the action of ginseng, the expression of apoptosis protein is increased and that of anti-apoptotic protein is reduced (Yoon et al.…”
Section: Discussionmentioning
confidence: 99%
“…При раке желудка и молочной железы у больных лучевая терапия на фоне высоких доз экстракта элеутерококка в меньшей степени подавляла иммунный статус и число лейкоцитов крови. Показано, что экстракты женьшеня, его полисахариды и гинзенозиды -протопанаксатриолы, панаксатриолы, а также Rh1, Rh20, R-Rh1, F1 -стимулируют продукцию оксида азота, интерлейкинов 4, 12, ИФН-γ иммунокомпетентными клетками [2,32,33].…”
Section: фитоадаптогены-иммуномодуляторыunclassified